THE IMPLEMENTATION OF LOCAL WISDOM IN ENVIRONMENTAL LEARNING IN THE GEOGRAPHY SUBJECT AT SMA NEGERI 1 KERJO, KARANGANYAR REGENCY - Gentur Adi Tjahjono; Afrida Mahavira Harmasita (Universitas Sebelas Maret (UNS), 2026)
Geography education plays a crucial role in enhancing students’ environmental awareness. One of the applicable approaches is the integration of local wisdom into the learning process. Local wisdom reflects the traditional ways communities have preserved environmental balance across generations. This study aims to (1) analyse the types of local wisdom in Kerjo District, (2) examine the implementation of local wisdom in geography learning, and (3) assess the impact of local wisdom on students’ understanding of environmental issues. This research employs a qualitative approach using a case study method conducted at SMA Negeri 1 Kerjo, which has implemented local wisdom-based learning. The research subjects include geography teachers and students. Data collection techniques involve observation, interviews, and analysis of teaching materials and school policy documents. The collected data were analysed through data reduction, data display, and conclusion drawing. The findings of the study are as follows: (1) Kerjo District has eight types of local wisdom, namely Nyadran, Bersih Desa, Tirakatan, Suran, Gotong Royong, Wetonan, Sedekah Bumi, and Rasulan; (2) The implementation of local wisdom-based education at SMA N 1 Kerjo is not yet optimal; (3) Students’ understanding of environmental topics in geography learning at SMA N 1 Kerjo needs improvement. This study highlights the importance of integrating local wisdom into geography education to strengthen students’ comprehension of environmental issues. It serves as a reference for educators and policymakers in developing more contextual and applicable culturally-based curricula in environmental education.